Uji Beda Keuntungan pada Usaha Gula Kelapa di Desa Pageraji Kabupaten Banyumas Jawa Tengah - Cahyaningtyas, Nur Indah; Rahmaningtyas, Avivah; Putri, Levana Masitajasmin; Fadhilah, Muhammad Luthfie; Novitaningrum, Restie; Fauziah, Irma (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The comparison between molded coconut sugar and crystal coconut sugar is in the production costs incurred such as the cooking process for crystal coconut sugar is longer than molded coconut sugar. In addition, the comparison of selling prices between the two causes different incomes, the income obtained affects the profits of the artisans. This study aims to examine the differences in profits of the molded coconut sugar and crystal coconut sugar business. The research method used is survey.The sample size determination was using simple random sampling method with the sample size obtained was 65 molded coconut sugar artisans and 39 crystal coconut sugar artisans. The data analysis method used was descriptive analysis and comparative profit analysis molded coconut sugar and crystal coconut sugar. The average profit received by artisans in the molded coconut sugar business is Rp1.064.123.00 per month with an R/C value of 1,55, while the average profit received by artisans in the crystal coconut sugar business is Rp1.449.228.00 per month with an R/C value of 1,71. The analysis of the difference in profit test resulted in a real difference in profit between the molded coconut sugar and crystal coconut sugar businesses. This difference in profit is caused by differences in the average selling price, production volume, revenue, production costs of molded coconut sugar artisans and crystal coconut sugar artisans.